Unionism in academic institutions in Central Mindanao - Merced Jr., Briccio M. (Notre Dame University, 1997)
The study aims to find whether there exists a relationship between knowledge on unionism, job satisfaction, and organizational climate. It also seeks to find out whether correlations exist among knowledge on unionism, job satisfaction, organizational climate and some personal variables as faculty rank, teaching experience, administrative experience, and educational attainment.